(untitled) (Applied Biological Research, 2023)
In present study, ecofriendly biological treatment of tannery effluent was performed by using unicellular microalga Tetradesmus obliquus strain RDRL01, isolated from Sipcot, Vellore, Tamil Nadu (India). The microalga reduced heavy metals content viz., chromium, cobalt, nickel, cadmium, lead, zinc and copper by 99.1, 98.2, 97.4, 94.3, 98.3, 96.8 and 96.3%, respectively, after 15 days treatment of tannery effluent. Treated effluent had 3.51 g biomass L-1 and treated effluent biomass contained 330.5 mg carbohydrate g-1 and yielded 13.5 mL bioethanol g-1. The functionagroups identified by Fourier transform infrared analysis were carboxylic acids, alkyl, hydroxyl, and carbonyl. Purified bioethanol was confirmed by HPLC, and chromatogram peak showed the retention time of 5.35 min. Microalgae T. obliquus RDRL01 demonstrated good biosorption efficiency and removed various toxic heavy metal pollutants from tannery effluent.